Heat sealing film and method for separating and recovering same
The heat-sealing film with a water-soluble resin composition addresses the challenge of separating and recovering packaging material layers under mild conditions, ensuring high humidity resistance and efficient solubility for recycling.
Patent Information
- Application Number
- JP2021122913
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-07-28
- Publication Date
- 2025-01-23
- Estimated Expiration
- 2041-07-28
AI Technical Summary
Existing recycling technologies face challenges in efficiently separating and recovering packaging material layers under mild conditions without compromising heat-sealing strength, especially under high humidity, due to insufficient solubility of intervening layers in solvents.
A heat-sealing film with a water-soluble resin composition as the outermost layer, containing a hydroxyl group-containing resin and alkali metal ions, which maintains heat-sealing strength under high humidity and can be easily dissolved in aqueous solutions for separation and recovery.
The film achieves excellent separation and recovery properties while maintaining heat-sealing strength, allowing for high-purity recovery of layers without deteriorating the performance of the packaging material, thus enhancing recyclability.
Smart Images

Figure 0007620513000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a heat-sealable film in which a heat-sealable layer can be easily dissolved and removed, and layers other than the heat-sealable layer can be separated and recovered with high purity, and a method for separating and recovering the same. [Background technology]
[0002] Packaging materials, including food packaging, are made by laminating a variety of materials with various functions such as heat resistance, mechanical properties, gas barrier properties, heat sealability, etc. For example, polyesters are widely used to improve heat resistance, polyamides to improve mechanical properties, ethylene-vinyl alcohol copolymers and polyvinylidene chloride to improve gas barrier properties, and various polyolefins such as polyethylene and polypropylene to improve heat sealability.
[0003] Meanwhile, in recent years, triggered by environmental and waste problems, there has been a worldwide demand for so-called post-consumer recycling (hereinafter sometimes simply abbreviated as recycling), which involves collecting and recycling packaging materials consumed in the market. In this regard, packaging materials are required to be composed of a single material as much as possible (mono-materialization), which allows for the production of high-purity, high-quality recycled raw materials. On the other hand, when mono-materialization is difficult, a method has been proposed in which layers that hinder recyclability are peeled off from each other and each is separated and recovered individually. Patent Document 1 describes the idea of providing an intervening layer between base layers made of different materials and facilitating recycling by separating them by immersion in a solvent. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2020 / 166685 Summary of the Invention [Problem to be solved by the invention]
[0005] In recent years, various recycling technologies have been considered. In a technology for separating adjacent substrate layers made of different materials in a solution, as described in Patent Document 1, it is necessary to recover each separated layer individually and without mixing them. However, in a recycling technology that requires separation in a short time or under mild conditions, the intervening layer does not dissolve sufficiently, and there are problems with the processability and separation and recovery accuracy.
[0006] On the other hand, the present inventors have found that the use of a solvent-soluble layer as a heat-sealing layer can broaden the range of film manufacturing methods and the range of layer configurations of packaging materials, and have begun to study this possibility. However, it has been found that the heat seal strength, particularly under high humidity conditions, may decrease as a result of increasing the solubility in a solvent in order to improve the processability and separation and recovery properties as described above.
[0007] The present invention has been made to solve the above problems, and aims to provide a heat-sealable film having a heat-sealable layer that is soluble in an aqueous solution and has excellent separation and recovery properties and heat-sealing strength under high humidity, and a method for separating and recovering the same. [Means for solving the problem]
[0008] The above issues are: [1] A heat-sealable film comprising a heat-sealable layer (X) made of a water-soluble resin composition (S) as one outermost layer, and a water-insoluble base layer (Z) containing at least one selected from the group consisting of a thermoplastic resin, paper and a metal foil as the other outermost layer, wherein the water-soluble resin composition (S) has an equilibrium moisture content of 3% by mass or more and 10% by mass or less at a temperature of 23°C and a relative humidity of 50%, the water-soluble resin composition (S) contains a hydroxyl group-containing resin (A) having a melting point of 220°C or less as a main component, and the water-soluble resin composition (S) contains alkali metal ions (B) in an amount of 100 ppm or more and 2000 ppm or less; [2] The heat-sealable film of [1], in which the heat-sealing layer (X) is directly laminated onto the base layer (Z); [3] The heat-sealable film of [1], further comprising an adhesive layer (Y), in which the heat-sealable layer (X) is laminated on the base layer (Z) via the adhesive layer (Y); [4] The heat-sealable film according to [3], wherein the heat-sealing layer (X), the adhesive layer (Y) and the base layer (Z) are a co-extruded film or a part thereof; [5] The heat-sealable film according to any one of [1] to [4], wherein the base layer (Z) is composed of a plurality of layers; [6] The heat-sealable film according to any one of [1] to [5], wherein the hydroxyl-containing resin (A) is a vinyl alcohol polymer (A1); [7] The heat-sealable film according to [6], wherein the vinyl alcohol polymer (A1) has a viscosity-average degree of polymerization of 400 or more and 2,000 or less; [8] The heat-sealable film according to [6] or [7], wherein the degree of saponification of the vinyl alcohol polymer (A1) is 70 mol % or more and 95 mol % or less; [9] The heat-sealable film of any of [1] to [8], wherein the water-soluble resin composition (S) contains 5% by mass or more and 40% by mass or less of a plasticizer (C), and the plasticizer (C) is at least one selected from the group consisting of glycerin, polyethylene glycol, polypropylene glycol, polyglycerin, mannitol, sorbitol, and pentaerythritol;
[10] The heat-sealable film according to any one of [1] to [9], having a total thickness of 20 μm or more and 350 μm or less, and a thickness ratio of the heat-sealable layer (X) to the total thickness of 1% or more and 20% or less;
[11] The oxygen permeability at 20°C and 65% relative humidity, measured according to JIS K 7126-2 (isobaric method; 2006), is 10cc / (m 2 a heat-sealable film according to any one of [1] to
[10] , which has a viscosity of 100 / sq.m. / day / atm or less;
[12] The moisture permeability measured according to JIS Z 0208 (1976) at a temperature of 40°C and a relative humidity of 90% is 50g / (m 2 a heat-sealable film according to any one of [1] to
[11] , wherein the drying time is 1-4 days or less;
[13] A heat-sealable film according to any one of [1] to
[12] , in which the heat-sealable layers (X) are placed face to face and pressed together for one second using a hot plate heat sealer at a temperature of 185°C and a pressure of 0.1 MPa, resulting in a heat seal strength of 1 N / 15 mm or more;
[14] The heat-sealable film according to any one of [1] to
[13] , in which, when cut into a 2 cm square and stirred in an aqueous solution (W) at 50°C, the heat-sealable layer (X) is dissolved and removed within 5 minutes;
[15] A packaging material comprising any one of the heat-sealable films described in [1] to
[14] ;
[16] A method for separating and recovering the film for heat sealing according to any one of [1] to
[14] , comprising contacting the film with an aqueous solution (W) at a temperature of 20°C or higher and 98°C or lower to dissolve the heat-sealable layer (X) and recovering the film from which the heat-sealable layer (X) has been removed; This is solved by providing: Effect of the Invention
[0009] According to the present invention, it is possible to provide a heat-sealable film having a heat-sealable layer that is soluble in an aqueous solution and that is excellent in separation and recovery properties and heat-sealing strength under high humidity, and a method for separating and recovering the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] In this specification, "thermal adhesive layer" means a layer that can be thermally fused. "Soluble in aqueous solution" means soluble in the aqueous solution (W) described below. "Separation and recovery" means the property that the thermal adhesive layer (X) does not remain when recovering a film from which the thermal adhesive layer (X) has been removed by the separation and recovery method of the present invention (the property that the thermal adhesive layer (X) dissolves sufficiently), and can be specifically evaluated by the method described in the Examples. "Heat seal strength under high humidity" means the T-peel strength after the thermal adhesive layer of the heat-sealable film of the present invention is heat-sealed and stored under high humidity, and can be specifically evaluated by the method described in the Examples.
[0011] The heat-sealable film of the present invention comprises a heat-sealable layer (X) made of a water-soluble resin composition (S) on one outermost layer, and a water-insoluble base layer (Z) containing at least one selected from the group consisting of thermoplastic resins, paper, and metal foil on the other outermost layer, the water-soluble resin composition (S) has an equilibrium moisture content of 3% to 10% by mass at a temperature of 23°C and a relative humidity of 50%, the water-soluble resin composition (S) contains a hydroxyl-containing resin (A) (hereinafter, sometimes simply abbreviated as "hydroxyl-containing resin (A)") having a melting point of 220°C or less as a main component, and the water-soluble resin composition (S) contains an alkali metal ion (B) in an amount of 100 ppm to 2000 ppm. The heat-sealable film of the present invention can exhibit the effects of excellent heat sealability under high humidity and excellent separation and recovery properties by comprising a heat-sealable layer (X) made of a water-soluble resin composition (S) on one outermost layer. In addition, various functions such as heat resistance, mechanical properties, and gas barrier properties required depending on the type of the base layer (Z) provided on the other outermost layer can be imparted. Furthermore, when the equilibrium moisture content of the water-soluble resin composition is within a specific range, it tends to be possible to achieve both solubility in an aqueous solution and heat seal strength under high humidity. Furthermore, when the water-soluble resin composition (S) contains a hydroxyl-containing resin (A) having a melting point of 220°C or less as a main component, it tends to improve heat fusion properties. Furthermore, when the water-soluble resin composition (S) contains a specific amount of alkali metal ions (B), it tends to be possible to achieve both solubility in an aqueous solution and heat seal strength under high humidity. Therefore, the heat-sealable film of the present invention exhibits sufficient heat sealability under normal use conditions as a packaging material, while the heat-sealable layer can be easily dissolved and removed after use as a packaging material, and layers other than the heat-sealable layer can be separated and recovered with high purity. Furthermore, by selecting the base layer, it is possible to improve recyclability without deteriorating the performance and quality of the packaging material, and contribute to the realization of a recycling-oriented society.
[0012] (Thermal adhesive layer (X)) The heat-sealable film of the present invention has a heat-sealable layer (X) made of a water-soluble resin composition (S) on one outermost layer. The heat-sealable layer (X) is excellent in heat-sealability and water-solubility, and imparts heat-sealability and recyclability (separation and recovery) to the heat-sealable film of the present invention. The heat-sealable layer (X) used in the present invention is a layer in which the main component is dissolved in an aqueous solution (W), and may be a layer in which the main component is dissolved by contacting with an aqueous solution (W) at 20°C to 98°C.
[0013] The thickness of the heat-sealable layer (X) is preferably from 5 μm to 50 μm, more preferably from 15 μm to 30 μm, from the viewpoints of heat sealability and dissolving and removing properties.
[0014] (Water-soluble resin composition (S)) The water-soluble resin composition (S) has an equilibrium moisture content of 3% by mass or more and 10% by mass or less at a temperature of 23° C. and a relative humidity of 50%. The lower limit of the equilibrium moisture content at a temperature of 23° C. and a relative humidity of 50% is preferably 5% by mass, and the upper limit is preferably 8% by mass. If the equilibrium moisture content is less than the lower limit, the water solubility of the heat-sealable layer (X) made of the water-soluble resin composition (S) becomes insufficient, and the separation and recovery properties tend to deteriorate. On the other hand, if the equilibrium moisture content exceeds the upper limit, the appearance of the heat-sealed portion of the heat-sealable layer (X) made of the water-soluble resin composition (S) and the heat-sealing strength under high humidity tend to deteriorate.
[0015] (Hydroxyl-containing resin (A)) The water-soluble resin composition (S) contains a hydroxyl-containing resin (A) having a melting point of 220°C or less as a main component. The water-soluble resin composition (S) contains the hydroxyl-containing resin (A) as a main component, and thus the heat sealability and water solubility of the heat-sealable layer (X) tend to be exhibited. Here, "containing as a main component" means containing more than 50 mass%. The hydroxyl-containing resin (A) means a resin containing a hydroxyl group, and from the viewpoint of increasing the solubility in the aqueous solution (W) described later, the ratio of the monomer units having a hydroxyl group in the total monomer units of the hydroxyl-containing resin (A) is preferably 80 mol% or more, more preferably 85 mol% or more, and may be 90 mol% or more or 95 mol% or more. On the other hand, the ratio of the monomer units having a hydroxyl group in the total monomer units of the hydroxyl-containing resin (A) may be 99 mol% or less. In order to improve the melt moldability and heat fusion property, the melting point of the hydroxyl-containing resin (A) is preferably 200°C or less, and more preferably 180°C or less. There is no particular lower limit for the melting point of the hydroxyl-containing resin (A), but from the viewpoint of maintaining heat resistance as a packaging material, it is generally 100° C. or higher, and may be 150° C. or higher.
[0016] Examples of the hydroxyl group-containing resin (A) include starch-based polymer components such as corn starch, cellulose-based polymers such as carboxymethyl cellulose and carboxyethyl cellulose, acrylic acid-based polymers such as sodium polyacrylate, vinyl alcohol-based polymers such as polyvinyl alcohol, etc. Among these, vinyl alcohol-based polymers (A1) are preferred from the viewpoints of melt moldability, solution stability, heat fusion, biodegradability, and adhesion to the adhesive layer (Y) described below.
[0017] The vinyl alcohol polymer (A1) is a polymer containing a vinyl alcohol unit. Examples of the vinyl alcohol polymer (A1) include polyvinyl alcohol (hereinafter, sometimes referred to as "PVA") obtained by homopolymerizing a vinyl ester and saponifying it, and modified PVA having other modifying groups. The modified PVA may be copolymerization modified or post-modified.
[0018] The viscosity average degree of polymerization of the vinyl alcohol polymer (A1) is preferably 400 or more and 2000 or less. The lower limit of the viscosity average degree of polymerization is more preferably 500, and even more preferably 700. When the viscosity average degree of polymerization is equal to or more than the lower limit, the thermal stability and heat fusion property of the vinyl alcohol polymer (A1) tend to be good. On the other hand, the upper limit of the viscosity average degree of polymerization is more preferably 1500, and even more preferably 1000. When the viscosity average degree of polymerization is equal to or less than the upper limit, the melt moldability and water solubility of the vinyl alcohol polymer (A1) tend to be good.
[0019] The viscosity average degree of polymerization of the vinyl alcohol polymer (A1) is measured in accordance with JIS K 6726:1994. Specifically, the intrinsic viscosity [η] (liters / g) of the vinyl alcohol polymer (A1) is measured in water at 30° C., and the viscosity average degree of polymerization P is calculated by the following formula using the intrinsic viscosity [η] value. When the degree of saponification of the vinyl alcohol polymer (A1) is less than 99.5 mol%, it is saponified to a degree of saponification of 99.5 mol% or more, and then the intrinsic viscosity [η] is measured. P = ([η] × 104 / 8.29) (1 / 0.62)
[0020] The saponification degree of the vinyl alcohol polymer (A1) is preferably 70 mol% or more, more preferably 75 mol% or more, and even more preferably 85 mol% or more. When the saponification degree is 70 mol% or more, the water solubility of the vinyl alcohol polymer (A1) is excellent, and the separation and recovery property of the heat sealable film is improved. The saponification degree of the vinyl alcohol polymer (A1) is preferably 95 mol% or less, more preferably 93 mol% or less, and even more preferably 90 mol% or less. When the saponification degree is 95 mol% or less, the melt moldability of the vinyl alcohol polymer (A1) is excellent. The saponification degree of the vinyl alcohol polymer (A1) is measured in accordance with JIS K6726:1994.
[0021] The vinyl alcohol polymer (A1) may contain monomer units other than vinyl alcohol units and vinyl ester units, so long as the effects of the present invention are not impaired. Examples of such monomers include α-olefins such as ethylene, propylene, n-butene, and isobutylene; acrylic acid and its salts; acrylic acid esters; methacrylic acid and its salts; methacrylic acid esters; acrylamide; acrylamide derivatives such as N-methylacrylamide, N-ethylacrylamide, N,N-dimethylacrylamide, diacetoneacrylamide, acrylamidopropanesulfonic acid and its salts, acrylamidopropyldimethylamine and its salts or its quaternary salts, and N-methylolacrylamide and its derivatives; methacrylamide; methacrylamide derivatives such as N-methylmethacrylamide, N-ethylmethacrylamide, methacrylamidopropanesulfonic acid and its salts, methacrylamidopropyldimethylamine and its salts or its quaternary salts, and N-methylolmethacrylamide and its derivatives; Examples of the vinyl ethers include methyl vinyl ether, ethyl vinyl ether, n-propyl vinyl ether, i-propyl vinyl ether, n-butyl vinyl ether, i-butyl vinyl ether, t-butyl vinyl ether, dodecyl vinyl ether, and stearyl vinyl ether; nitriles such as acrylonitrile and methacrylonitrile; vinyl halides such as vinyl chloride and vinyl fluoride; vinylidene halides such as vinylidene chloride and vinylidene fluoride; allyl compounds such as allyl acetate and allyl chloride; unsaturated dicarboxylic acids and their salts or esters such as maleic acid, itaconic acid, and fumaric acid; vinyl silyl compounds such as vinyltrimethoxysilane; and isopropenyl acetate. The content of these monomers varies depending on the purpose and application of use, but is preferably 10 mol% or less, more preferably less than 5 mol%, even more preferably less than 3 mol%, particularly preferably less than 1 mol%, and may be 0 mol%. The vinyl alcohol polymer (A1) may contain one type alone or two or more types.
[0022] (Alkali metal ion (B)) The water-soluble resin composition (S) contains 100 ppm or more and 2000 ppm or less of alkali metal ions (B). The lower limit of the content of alkali metal ions (B) is more preferably 300 ppm, and even more preferably 500 ppm. If the content of alkali metal ions (B) is less than the above lower limit, the thermal stability of the water-soluble resin composition (S) decreases, the adhesion to the adhesive layer (Y) described below decreases, and the heat seal strength under high humidity becomes insufficient. In addition, the water solubility of the water-soluble resin composition (S) decreases. On the other hand, the upper limit of the content of alkali metal ions (B) is more preferably 1500 ppm, and even more preferably 1000 ppm. If the content of alkali metal ions (B) exceeds the above upper limit, the water-soluble resin composition (S) tends to be colored, and the heat seal strength under high humidity becomes insufficient.
[0023] Examples of the alkali metal ion (B) include a lithium ion, a sodium ion, and a potassium ion. From the viewpoint of economic efficiency and balance of physical properties, the sodium ion or the potassium ion is preferred, and the sodium ion is more preferred.
[0024] The alkali metal ion (B) may be present in a state dissociated from an anion constituting an alkali metal salt, or in a state of a salt bonded to an anion, or may be present in a state coordinated to a group (e.g., a carboxyl group, a hydroxyl group, etc.) possessed by the vinyl alcohol polymer (A1) or other optional components.
[0025] The alkali metal ion (B) is usually derived from a salt, but the components constituting the alkali metal ion (B) are not particularly limited, and fatty acid metal salts, metal salts other than fatty acid metal salts (nitrates, sulfates, etc.), etc. can also be used.
[0026] The fatty acid metal salt may be a higher fatty acid metal salt having 12 or more carbon atoms or a fatty acid metal salt having 11 or less carbon atoms. From the viewpoint of improving the thermal stability of the water-soluble resin composition (S), a higher fatty acid metal salt having 12 or more carbon atoms is preferred, and from the viewpoint of improving the water solubility of the water-soluble resin composition (S), a fatty acid metal salt having 11 or less carbon atoms is preferred. Examples of higher fatty acid metal salts having 12 or more carbon atoms include metal salts of fatty acids such as lauric acid, lauric acid, tridecylic acid, myristic acid, pentadecylic acid, palmitic acid, heptadecylic acid, stearic acid, hydroxystearic acid, nonadecanoic acid, oleic acid, behenic acid, montanic acid, and linoleic acid. Examples of fatty acid metal salts having 11 or less carbon atoms include acetates and propionates. These may be contained alone or in a mixture of two or more.
[0027] The water-soluble resin composition (S) of the present invention preferably further contains 5% by mass or more and 40% by mass or less of a plasticizer (C). By containing the plasticizer (C), the melt moldability, heat fusion property, and solubility in the aqueous solution (W) described below of the vinyl alcohol polymer (A1) are improved. The molecular weight of the plasticizer (C) is not particularly limited, but is preferably 10,000 or less, more preferably 2,000 or less, further preferably 200 or less, and particularly preferably 100 or less, from the viewpoint of improving water solubility. The lower limit of the content of the plasticizer (C) is more preferably 10% by mass. The upper limit of the content of the plasticizer (C) is more preferably 30% by mass. The plasticizer (C) is preferably at least one selected from the group consisting of glycerin, polyethylene glycol, polypropylene glycol, polyglycerin, mannitol, sorbitol, and pentaerythritol, more preferably at least one selected from the group consisting of glycerin, polyethylene glycol, mannitol, and sorbitol, even more preferably at least one selected from the group consisting of glycerin, mannitol, and sorbitol, and particularly preferably glycerin.
[0028] The water-soluble resin composition (S) may contain other components other than the hydroxyl group-containing resin (A), the alkali metal ion (B), and the plasticizer (C) as long as the effects of the present invention are not impaired. Examples of other components include polyvalent metal ions, carboxylic acids, phosphoric acid compounds, oxidation promoters, antioxidants, heat stabilizers (melt stabilizers), photoinitiators, deodorants, ultraviolet absorbers, antistatic agents, lubricants, colorants, fillers, drying agents, bulking agents, pigments, dyes, processing aids, flame retardants, and antifogging agents. The content of other components in the water-soluble resin composition (S) is usually 5% by mass or less, preferably 3% by mass or less, and more preferably 1% by mass or less.
[0029] The proportion of the hydroxyl-containing resin (A) in the water-soluble resin composition (S) is preferably 60% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, particularly preferably 90% by mass or more, and may be 95% by mass or more, 97% by mass or more, 98% by mass or more, or 99% by mass or more. The proportion of the hydroxyl-containing resin (A) in the total resins constituting the water-soluble resin composition (S) is preferably 70% by mass or more, more preferably 90% by mass or more, even more preferably 95% by mass or more, particularly preferably 99% by mass or more, and the total resins constituting the water-soluble resin composition (S) may be substantially composed of only the hydroxyl-containing resin (A). The proportion of the hydroxyl-containing resin (A) and the alkali metal ion (B) in the water-soluble resin composition (S) is preferably 70% by mass or more, more preferably 90% by mass or more, even more preferably 95% by mass or more, and particularly preferably 99% by mass or more, and the water-soluble resin composition (S) may be substantially composed of only the hydroxyl-containing resin (A) and the alkali metal ion (B). When the water-soluble resin composition (S) contains a plasticizer (C), the proportion of the hydroxyl-containing resin (A), the alkali metal ion (B), and the plasticizer (C) in the water-soluble resin composition (S) is preferably 70% by mass or more, more preferably 90% by mass or more, even more preferably 95% by mass or more, and particularly preferably 99% by mass or more, and the water-soluble resin composition (S) may be substantially composed of only the hydroxyl-containing resin (A), the alkali metal ion (B), and the plasticizer (C).
[0030] The method of preparing the water-soluble resin composition (S) of the present invention is not particularly limited, and any method may be used as long as it can uniformly mix the hydroxyl-containing resin (A), the alkali metal ion (B), and if necessary, the plasticizer (C) and other components. For example, the water-soluble resin composition (S) can be prepared by blending the hydroxyl-containing resin (A), the alkali metal ion (B), and if necessary, the plasticizer (C) and other components, and then melt-kneading and pelletizing the mixture; the method of pre-introducing the alkali metal ion (B) into the hydroxyl-containing resin (A), then blending the plasticizer (C) and other components as necessary, and then melt-kneading and pelletizing the mixture; the method of pre-introducing the alkali metal ion (B) into the hydroxyl-containing resin (A), then blending the plasticizer (C) and other components as necessary, and then melt-kneading and pelletizing the mixture; the method of pre-introducing the alkali metal ion (B) into the hydroxyl-containing resin (A), then feeding the plasticizer (C) and other components as necessary, and then kneading and pelletizing the mixture in a melt kneader at a fixed ratio.
[0031] (Base material layer (Z)) The heat-sealable film of the present invention comprises a water-insoluble base layer (Z) containing at least one selected from the group consisting of thermoplastic resins, paper and metal foils, as the outermost layer opposite to the heat-sealable layer (X). Examples of the thermoplastic resin constituting the base layer (Z) include various polyolefins (polyethylene, polypropylene, poly1-butene, poly4-methyl-1-pentene, ethylene-propylene copolymers, copolymers of ethylene and α-olefins having 4 or more carbon atoms, copolymers of polyolefins and maleic anhydride, ethylene-vinyl ester copolymers, ethylene-vinyl alcohol copolymers, ethylene-acrylic acid ester copolymers, or modified polyolefins obtained by graft-modifying these with unsaturated carboxylic acids or their derivatives, etc.), various polyamides (nylon 6, nylon 6·6, nylon 6 / 66 copolymers, nylon 11, nylon 12, polymetaxylylene adipamide, etc.), various polyesters (polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, etc.), polyvinyl chloride, polyvinylidene chloride, polystyrene, polyacrylonitrile, polyurethane, polycarbonate, polyacetal, polyacrylate, etc. Among these, from the viewpoint of excellent balance between heat resistance and mechanical properties, the thermoplastic resin constituting the base layer (Z) is preferably polyethylene terephthalate.
[0032] The thermoplastic resin constituting the base layer (Z) may contain various additives as long as the effects of the present invention are not impaired. Examples of such additives include heat stabilizers, antioxidants, UV absorbers, plasticizers, antistatic agents, lubricants, colorants, fillers, stabilizers, surfactants, drying agents, crosslinking agents, and fiber reinforcement agents. The content of additives in the thermoplastic resin is usually 5% by mass or less, preferably 3% by mass or less, and more preferably 1% by mass or less.
[0033] Examples of the paper constituting the base layer (Z) include various natural papers and synthetic papers, etc. Examples of the metal foil constituting the base layer (Z) include at least one metal foil selected from the group consisting of gold, silver, copper, nickel, stainless steel, magnesium alloy, and aluminum, etc., and aluminum foil is preferred from the viewpoints of economy and gas barrier properties.
[0034] The base layer (Z) may be a single layer or may have a multilayer structure consisting of multiple layers. When the base layer (Z) is a multilayer structure, the number of layers is preferably 2 to 9 from the viewpoint of economically imparting functions such as gas barrier properties. The thickness of the base layer (Z) is preferably 10 μm to 300 μm, more preferably 25 μm to 150 μm, and may be 75 μm to 150 μm from the viewpoint of handling properties as a packaging material and resource saving. When the base layer (Z) is a multilayer structure, it is preferable that the base layer (Z) has an inorganic vapor deposition layer (I) described later from the viewpoint of efficiently imparting gas barrier properties.
[0035] The method for forming the multilayer structure of the base layer (Z) is not particularly limited, and examples thereof include known lamination methods such as dry lamination, co-injection molding, co-extrusion molding, etc. Co-extrusion molding methods include co-extrusion lamination, co-extrusion film / sheet molding, co-extrusion blow molding, etc. These methods may be used in combination.
[0036] The base layer (Z) may include an inorganic vapor deposition layer (I). The inorganic vapor deposition layer (I) is made of an inorganic material such as a metal or an inorganic oxide, and means a layer having gas barrier properties against oxygen and water vapor. The thickness of the inorganic vapor deposition layer (I) is generally less than 500 nm. When the thickness is less than 500 nm, the viscosity stability is excellent when the pulverized material of the multilayer structure including the inorganic vapor deposition layer (I) is melt-molded, and the generation of gels and lumps can be suppressed, so that the recyclability tends to be excellent.
[0037] The inorganic vapor deposition layer (I) is preferably either a metal vapor deposition layer or an inorganic oxide vapor deposition layer. When light-shielding properties are to be imparted, a metal vapor deposition layer is preferred, but from the viewpoints of visibility of the contents as a packaging material, suitability for use in a microwave oven, and suppression of the generation of gels and lumps when pulverized materials are melt-molded, an inorganic oxide vapor deposition layer is preferred.
[0038] The metal vapor deposition layer is generally a layer containing aluminum as a main component. The content of aluminum atoms in the metal vapor deposition layer is preferably 50 mol% or more, more preferably 70 mol% or more, even more preferably 90 mol% or more, and particularly preferably 95 mol% or more. The average thickness of the metal vapor deposition layer is preferably 120 nm or less, more preferably 100 nm or less, and even more preferably 90 nm or less. The average thickness of the metal vapor deposition layer is preferably 25 nm or more, more preferably 35 nm or more, and even more preferably 45 nm or more. The average thickness of the metal vapor deposition layer is the average thickness at any 10 points on the cross section of the metal vapor deposition layer measured by an electron microscope. When the base layer (Z) has a metal vapor deposition layer, the light transmittance at a wavelength of 600 nm can be 10% or less, and the light shielding property is excellent.
[0039] The inorganic oxide deposition layer may be a deposition film of an inorganic oxide, such as an oxide of silicon, aluminum, magnesium, calcium, potassium, tin, sodium, boron, titanium, lead, zirconium, or yttrium, preferably alumina (aluminum oxide) or silica (silicon oxide). The average thickness of the inorganic oxide deposition layer is preferably 60 nm or less, more preferably 50 nm or less, and even more preferably 40 nm or less. The average thickness of the inorganic oxide deposition layer is preferably 10 nm or more, more preferably 15 nm or more, and even more preferably 20 nm or more. The average thickness of the inorganic oxide deposition layer is the average thickness at any 10 points on the cross section of the inorganic oxide deposition layer measured by an electron microscope. When the base layer (Z) has an inorganic oxide deposition layer, the light transmittance at a wavelength of 600 nm can be 80% or more, and the visibility of the contents is excellent when used as a packaging material.
[0040] The inorganic vapor deposition layer (I) can be formed by a known physical vapor deposition method or chemical vapor deposition method. Specifically, examples of the method include vacuum vapor deposition, sputtering, ion plating, ion beam mixing, plasma CVD, laser CVD, MO-CVD, and thermal CVD. It is preferable to use a physical vapor deposition method, and it is particularly preferable to use a vacuum vapor deposition method. In addition, as long as the effect of the present invention is not hindered, a protective layer (topcoat layer) may be provided on the inorganic vapor deposition layer (I) as necessary. The upper limit of the surface temperature during the film formation of the inorganic vapor deposition layer (I) is preferably 60°C, more preferably 55°C, and even more preferably 50°C. In addition, the lower limit of the surface temperature during the film formation of the inorganic vapor deposition layer (I) is not particularly limited, but is preferably 0°C, more preferably 10°C, and even more preferably 20°C. Before the film formation, the film formation surface may be plasma-treated. The plasma treatment can be performed by a known method, and atmospheric pressure plasma treatment is preferable. In the atmospheric pressure plasma treatment, the discharge gas used may be nitrogen, helium, neon, argon, krypton, xenon, radon, etc. Among these, nitrogen, helium, and argon are preferably used, and nitrogen is particularly preferable because it can reduce costs.
[0041] (Adhesive layer (Y)) The heat-sealable film of the present invention preferably further has an adhesive layer (Y), and the heat-sealable layer (X) is laminated to the base layer (Z) via the adhesive layer (Y). By laminating the heat-sealable layer (X) to the base layer (Z) via the adhesive layer (Y), the adhesion between the layers is improved, the quality as a packaging material is improved, and the heat seal strength under high humidity is also improved. The heat-sealable film of the present invention preferably has the heat-sealable layer (X), the adhesive layer (Y), and the base layer (Z) laminated directly in this order. The thickness of the adhesive layer (Y) is preferably 0.5 to 25 μm, more preferably 1 to 15 μm.
[0042] The component constituting the adhesive layer (Y) preferably has an adhesive resin such as carboxylic acid-modified polyolefin or carboxylic acid-modified polyester as the main component, and more preferably is an adhesive resin such as carboxylic acid-modified polyolefin or carboxylic acid-modified polyester. Examples of carboxylic acid-modified polyolefin include modified olefin polymers containing carboxyl groups obtained by chemically bonding unsaturated carboxylic acid or its anhydride to an olefin polymer by addition reaction, graft reaction, or the like. Examples of unsaturated carboxylic acid or its anhydride include maleic acid, maleic anhydride, fumaric acid, acrylic acid, methacrylic acid, crotonic acid, itaconic acid, citraconic acid, hexahydrophthalic anhydride, and the like, and among them, maleic anhydride is preferably used. Specifically, one or a mixture of two or more selected from the group consisting of maleic anhydride graft-modified polyethylene, maleic anhydride graft-modified polypropylene, maleic anhydride graft-modified ethylene-propylene copolymer, maleic anhydride graft-modified ethylene-ethyl acrylate copolymer, maleic anhydride graft-modified ethylene-vinyl acetate copolymer, and the like are preferred. Adhesive resins can sometimes have improved adhesive properties when mixed with rubber or elastomer components such as polyisobutylene or ethylene-propylene rubber, or with polyolefin resins different from the base polyolefin resin of the adhesive resin.
[0043] The adhesive layer (Y) can also be formed by treating the surface of one of the layers (thermal adhesive layer (X) or base layer (Z)) with a known anchor coating agent, or by coating the surface of one of the layers with a known adhesive. As the anchor coating agent or adhesive, a two-liquid reactive polyurethane adhesive in which a polyisocyanate component and a polyol component are mixed and reacted is preferred. In addition, the adhesiveness may be further improved by adding a small amount of an additive such as a known silane coupling agent to the anchor coating agent or adhesive. Examples of the silane coupling agent include, but are not limited to, silane coupling agents having reactive groups such as an isocyanate group, an epoxy group, an amino group, a ureido group, and a mercapto group.
[0044] (Heat seal film) The heat-sealable film of the present invention may have a structure in which the heat-sealable layer (X) is directly laminated on the substrate layer (Z), or may have a structure in which the heat-sealable layer (X) is laminated on the substrate layer (Z) via the adhesive layer (Y). The heat-sealable layer (X), adhesive layer (Y) and substrate layer (Z) may be produced in separate processes and then laminated in a post-process such as a dry lamination method, or may be sequentially laminated by a solution coating method or the like, or may be produced in part or in whole simultaneously by a co-extrusion molding method or the like. That is, the heat-sealable film of the present invention may have the heat-sealable layer (X), adhesive layer (Y) and substrate layer (Z) as co-extruded films or parts thereof.
[0045] In producing the heat-sealing film of the present invention, it is sufficient to obtain a heat-sealing layer having a heat-sealing layer (X) as one outermost layer and a base layer (Z) as the other outermost layer, and for example, a heat-sealing film having a layer structure of (X) / (Z) or (X) / (Y) / (Z) is exemplified. The layer (Z) may itself be composed of a plurality of layers, and in the present invention, all layers other than the layer (X) and the layer (Y) are regarded as part or all of the layer (Z). From the viewpoint of achieving both handleability and functionality as a packaging material, the total thickness of the heat-sealing film of the present invention is preferably 20 μm or more and 350 μm or less, more preferably 60 μm or more and 200 μm or less. For the same reason, the thickness ratio of the heat-sealing layer (X) to the total thickness is preferably 1% or more and 20% or less.
[0046] The oxygen permeability of the heat-sealable film of the present invention is not particularly limited and may be adjusted depending on the application. However, the oxygen permeability of the film is preferably 10 cc / (m2) at a temperature of 20° C. and a relative humidity of 65%. 2 ·day·atm) or less is preferable, and 1cc / (m 2 ·day·atm) or less is preferable, and 0.1cc / (m 2It is more preferable that the oxygen permeability is equal to or less than 1000 kPa (days atm). A heat sealable film having an oxygen permeability in this range can suppress spoilage or deterioration of the contents and can maintain the quality of the contents for a long period of time. The oxygen permeability is measured in accordance with JIS K 7126-2 (isobaric method; 2006), and specifically, the method described in the examples is used.
[0047] The moisture permeability of the heat-sealable film of the present invention is not particularly limited and may be adjusted depending on the application. However, the moisture permeability at a temperature of 40° C. and a relative humidity of 90% is preferably 50 g / (m 2 ·day) or less, and 10g / (m 2 ·day) or less is more preferable, and 1g / (m 2 ·day) or less is even more preferable. A heat sealable film having a moisture permeability in this range can suppress spoilage or deterioration of the contents and can maintain the quality of the contents for a long period of time. The moisture permeability is measured in accordance with JIS Z 0208 (1976), and specifically, the method described in the examples is adopted.
[0048] The heat-sealing film of the present invention is preferably such that the heat-sealing strength obtained by placing the heat-fusible layers (X) of two heat-sealing films face each other and pressing them together for 1 second using a hot plate heat sealer under conditions of a temperature of 185°C and a pressure of 0.1 MPa is 1N / 15mm or more, more preferably 1.5N / 15mm or more, and even more preferably 2N / 15mm or more. When the heat-sealing strength is within the above range, the quality retention of the contents is good. The heat-sealing strength can be specifically measured by the method described in the Examples.
[0049] When the heat-sealable film of the present invention is cut into a 2 cm square and stirred in a 50° C. aqueous solution (W) described below, the heat-sealable layer (X) is preferably dissolved and removed within 5 minutes, more preferably within 3 minutes. When the heat-sealable layer (X) is dissolved and removed under the above conditions, separation and recovery are improved, which is preferable because recycling can be carried out economically. Here, dissolving and removing means that more than 75% by mass of the heat-sealable layer (X) is removed, preferably more than 90% by mass is removed, and more preferably it is completely dissolved and removed.
[0050] The heat-sealing film of the present invention can be made into a container or package (bag, cup, tube, tray, bottle, etc.) with the heat-sealing layer on the inside by overlapping the heat-sealing layers and heat-sealing the layers together. The heat-sealing film of the present invention exhibits sufficient heat-sealing properties under normal conditions of use as a packaging material, and the heat-sealing layer can be easily dissolved and removed after use as a packaging material, and layers other than the heat-sealing layer can be separated and recovered with high purity, so that it is preferable to use it as a packaging material for food, etc.
[0051] (Separation and recovery method) The separation and recovery method of the present invention is achieved by contacting the heat-sealing film of the present invention with an aqueous solution (W) at 20°C to 95°C to dissolve the heat-sealing layer (X) made of the water-soluble resin composition (S), and recovering the film from which the heat-sealing layer (X) has been removed. At this time, by increasing the temperature of the water or stirring it, it is expected that the effect of increasing the dissolution rate of the heat-sealing layer (X) and the effect of removing attached contaminants and the like can be expected. In addition, the size of the heat-sealing film dropped into the aqueous solution (W) is not particularly limited, but as an example, it is preferably smaller than 10 cm square, and may be about 2 cm square. After the dissolution and removal of the heat-sealing layer (X) is completed, the film remaining as an insoluble component is recovered, washed with pure water or the like as necessary, dried, and then melt-molded using an extruder, and can be re-pelletized as a recycled resin. Various molded bodies are manufactured using the pellets obtained in this way. Here, the aqueous solution (W) may be an aqueous solution containing a chloride salt such as sodium chloride, potassium chloride, calcium chloride, etc. as a solute, or may be water without a solute. Although there is no particular limitation on the pH range of the aqueous solution (W), the pH of the aqueous solution (W) is preferably in the range of 5 to 9, and may be in the range of 6 to 8 or 6.5 to 7.5, in order to greatly simplify the equipment and process required for dissolving and removing. The thermal adhesive layer (X) of the present invention has excellent solubility even in a pH range close to neutral, for example, pH 5 to 9, and can be easily dissolved and removed.
[0052] Whether the film from which the thermal adhesive layer (X) has been removed floats or sinks in the aqueous solution (W) is determined by the relative specific gravity of the film and the aqueous solution (W). In the case of a substance with a specific gravity greater than 1, such as polyester or ethylene-vinyl alcohol copolymer, it will sink in a normal aqueous solution, but if it is preferable to recover it by floating it, it is possible to recover it by floating it by adding a chloride salt such as sodium chloride, potassium chloride, or calcium chloride to the aqueous solution to increase the specific gravity of the aqueous solution. In this case, from the viewpoint of economy and handling, the concentration of the chloride salt, etc. required to express the required specific gravity w of the aqueous solution (W) is preferably 40 mass% or less. If the concentration exceeds 40 mass%, the procurement cost of the chloride salt, etc. will be excessive, and there is a risk of causing a problem in the washing process after separation.
[0053] Moreover, from the viewpoint of stability of the separation step, the concentration of the chloride salt, etc. required to realize the specific gravity w of the required aqueous solution (W) is preferably at least 10% by mass lower than the saturation concentration of the chloride salt, etc. If the difference between the concentration of the chloride salt, etc. required to realize the specific gravity w of the required aqueous solution (W) and the saturation concentration of the chloride salt, etc. is less than 10% by mass, it may take a long time to dissolve the chloride salt, etc., or the chloride salt, etc. may precipitate in the separation tank or in the material after separation, which may lead to instability of the process. EXAMPLES
[0054] The present invention will be described in more detail below using examples, but the present invention is not limited to these examples in any way.
[0055] Example 1 (1) Synthesis of PVA Vinyl acetate was polymerized by a conventional method to obtain a vinyl acetate polymer, which was then saponified by a conventional method to obtain PVA1 having a viscosity average degree of polymerization of 800 and a degree of saponification of 88 mol%. The viscosity average degree of polymerization and the degree of saponification of PVA1 were determined by the method described in JIS K6726 (1994). The temperature of the maximum endothermic peak of the obtained PVA1 was determined by heating it from 20°C to 250°C at a rate of 10°C / min using a differential scanning calorimeter DSC (TA Instrument's "Q2000"), and this was taken as the melting point. As a result, the melting point of the obtained PVA1 was 175°C.
[0056] (2) Production of PVA resin composition Next, 87 parts by mass of the obtained PVA1 and 13 parts by mass of glycerin as a plasticizer were mixed using a planetary mixer, and then an aqueous sodium acetate solution was added so that the sodium ion content was 800 ppm, and melt-kneaded to obtain PVA1 resin composition pellets. The melt-kneading was performed using a 25 mm extruder (D (mm) = 25, L / D = 25, compression ratio = 2.0, screws: same direction full intermeshing type) manufactured by Toyo Seiki Seisakusho Co., Ltd., so that the resin temperature was 220°C.
[0057] (3) Measurement of equilibrium moisture content of PVA resin composition The obtained PVA1 resin composition pellets were left to stand at a temperature of 23°C and a relative humidity of 50% for 30 days or more, and then dried at 120°C for 3 hours. The equilibrium moisture content was calculated based on the weight before and after drying, and evaluated according to the following criteria. The results are shown in Table 1. Judgment criteria A: 5% by mass or more, less than 8% by mass BL: 3% by mass or more, less than 5% by mass BH: 8% by mass or more, less than 10% by mass CL: Less than 3% by mass CH: 10% by mass or more
[0058] (4) Manufacture of heat-sealable films Using a coextrusion multilayer cast film-forming device, a heat-sealable film (X) made of the PVA1 resin composition, an adhesive layer (Y) made of maleic anhydride grafted ethylene-vinyl acetate copolymer (Dow Chemical Japan Co., Ltd.'s "Binel 3810", adhesive layer (Y1)), and a base layer (Z) made of polyethylene terephthalate (Bellpet EFG70 made by Bell Polyester Products Co., Ltd.) (a three-type three-layer coextrusion multilayer cast film having a layer thickness and layer structure of (X) / (Y) / (Z)=20μm / 10μm / 100μm) was obtained. The film-forming conditions at this time are shown below. Co-extrusion conditions Extrusion temperature of heat-sealing layer (X): Feeding section / compression section / metering section / die = 180 / 220 / 220 / 270℃ Extrusion temperature of adhesive layer (Y): feeding section / compression section / metering section / die = 150 / 200 / 200 / 270℃ Extrusion temperature of base layer (Z): feeding section / compression section / metering section / die = 240 / 260 / 270 / 270℃ Extruder Heat-sealing layer (X): 32φ extruder UT-32-H type (manufactured by Plastics Engineering Research Institute Co., Ltd.) Adhesive layer (Y): 40φ extruder GT-40-A type (manufactured by Plastics Engineering Research Institute Co., Ltd.) Base layer (Z): 65φ extruder SZW65GT-22MG-STD type (manufactured by Technovel Co., Ltd.) T-die: 600mm width (Cloeren Incorporated) Cooling roll temperature: 60℃
[0059] (5) Appearance characteristic evaluation The heat-sealable film obtained in (4) above was visually evaluated and judged according to the following criteria. The results are shown in Table 1. Judgment criteria A: The appearance is uniform and not discolored. B1: There are defects such as blemishes. B2: Discoloration (yellowing) is observed B3: Unevenness due to thickness variation is observed
[0060] (6) Heat seal strength measurement The heat-sealable layers (X) of the heat-sealable films obtained in (4) above were placed face to face, and heat-sealed by pressing for 1 second at a temperature of 185°C and a pressure of 0.1MPa using a hot plate heat sealer. The film was conditioned for 7 days in an atmosphere of 40°C and 90% RH, and then a rectangular test piece with a width of 15 mm was cut out. The T-type peel strength (N / 15 mm) of the obtained test piece was measured using an "Autograph AGS-H" manufactured by Shimadzu Corporation under conditions of a chuck interval of 50 mm and a tensile speed of 300 mm / min. Measurements were performed on five test pieces, and the average value was used to make a judgment according to the following criteria. The results are shown in Table 1. Judgment criteria A:2.0N / 15mm or more B: 1.5N / 15mm or more, less than 2.0N / 15mm C: 1.0N / 15mm or more, less than 1.5N / 15mm D: 0.5N / 15mm or more, less than 1.0N / 15mm E: Less than 0.5N / 15mm
[0061] (7) Oxygen permeability measurement The heat seal film obtained in (4) above was subjected to oxygen permeability measurement with the base layer (Z) side as the oxygen supply side and the heat fusion layer (X) side as the carrier gas side. Specifically, the oxygen permeability measurement device ("MOCON OX-TRAN2 / 21" manufactured by Modern Control) was used to measure the oxygen permeability (unit: cc / (m)) under the conditions of temperature 20°C, humidity 65% RH on the oxygen supply side, humidity 65% RH on the carrier gas side, oxygen pressure 1 atm, and carrier gas pressure 1 atm. 2 The solubility in water of 1000 ml was measured and rated according to the following criteria. Nitrogen gas containing 2% by volume of hydrogen gas was used as the carrier gas. The results are shown in Table 1. Judgment criteria A: 0.1cc / (m 2 ·day·atm) B: 0.1cc / (m 2 ·day · atm) or more, 1cc / (m 2 ·day·atm) C: 1cc / (m 2 ·day · atm) or more, 10cc / (m2 ·day·atm) D: 10cc / (m 2 ·day · atm) or more, 50cc / (m 2 ·day·atm) E: 50cc / (m 2 ·day · atm) or more
[0062] (8) Moisture permeability measurement Granular calcium chloride dried at 120°C was filled into a metal cup with a volume of 50cc, and the heat-sealing film obtained in (4) above was placed on the lid of the cup and sealed with paraffin. The mass of this cup was measured, and then the mass was measured after storing it for 24 hours in a thermo-hygrostat at a temperature of 40°C and a relative humidity of 90%. The water vapor transmission rate was calculated from the surface area of the lid and the increase in mass of the cup, and was evaluated according to the following criteria. The results are shown in Table 1. Judgment criteria A: 1g / (m 2 Less than 1 day B: 1g / (m 2 ·day) or more, 10g / (m 2 Less than 1 day C: 10g / (m 2 ·day) or more, 50g / (m 2 Less than 1 day D: 50g / (m 2 ·day) or more, 100g / (m 2 Less than 1 day E: 100g / (m 2 1 day or more
[0063] (9) Separation and recovery evaluation The heat-sealing film obtained in (4) above was cut into 10 square pieces of 2 cm each to obtain test pieces for evaluation of separation and recovery. The obtained test pieces were stirred in 50°C warm water for 5 minutes, and the remaining film pieces were collected, lightly rinsed with 20°C cold water, and then dried in hot air at 120°C for 2 hours. The dried film pieces were measured using a differential scanning calorimeter DSC under the same conditions as in (1), and the change in the amount of heat absorbed by the heat-sealing layer (X) relative to the amount of heat absorbed by the base layer (Z) before and after the separation and recovery process was judged according to the following criteria. The results are shown in Table 1. Judgment criteria A: No endothermic reaction was observed in the heat-sealed layer (X) after separation and recovery. B: After separation and recovery, the heat absorption of the heat-sealed layer (X) was less than 10%. C: After separation and recovery, the heat absorption amount of the heat-sealed layer (X) was 10% or more and less than 25%. D: After separation and recovery, the heat absorption amount of the heat-sealed layer (X) was 25% or more and less than 50%. E: After separation and recovery, the heat absorption of the heat-sealed layer (X) was 50% or more.
[0064] Examples 2 to 5, Comparative Examples 1 and 2 A PVA resin composition and a heat-sealable film were prepared and evaluated in the same manner as in Example 1, except that the amount of the aqueous sodium acetate solution added was changed so that the sodium ion content was as shown in Table 1. The results are shown in Table 1.
[0065] Example 6 A PVA resin composition and a heat-sealable film were prepared and evaluated in the same manner as in Example 1, except that an aqueous potassium acetate solution was used instead of an aqueous sodium acetate solution and the potassium ion content was 800 ppm. The results are shown in Table 1.
[0066] Examples 7 to 9, Comparative Example 3 A PVA resin composition and a heat-sealable film were prepared and evaluated in the same manner as in Example 1, except that the content of glycerin was changed as shown in Table 1. The results are shown in Table 1.
[0067] Examples 10 to 12 Except for using mannitol, sorbitol and polyethylene glycol instead of glycerin, PVA resin compositions and heat-sealable films were prepared and evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0068] Example 13 A PVA resin composition and a heat-sealable film were prepared and evaluated in the same manner as in Example 1, except that PVA2 having a viscosity average degree of polymerization of 350 and a degree of saponification of 88 mol% was used instead of PVA1. The results are shown in Table 1.
[0069] Example 14 A PVA resin composition and a heat-sealable film were prepared and evaluated in the same manner as in Example 1, except that PVA3 having a viscosity average polymerization degree of 600 and a saponification degree of 80 mol% and PVA4 having a viscosity average polymerization degree of 800 and a saponification degree of 74 mol% were mixed in a ratio of (PVA3 / PVA4) 70 / 30 instead of PVA1, and no plasticizer was added. The results are shown in Table 1.
[0070] Example 15 A PVA resin composition and a heat-sealable film were prepared and evaluated in the same manner as in Example 1, except that PVA5 (modified PVA) with an ethylene modification degree of 8.5 mol%, a viscosity average polymerization degree of 350, and a saponification degree of 98 mol% was used instead of PVA1, and no plasticizer was added. The results are shown in Table 1.
[0071] Examples 16 to 20 Heat-sealable films were produced and evaluated in the same manner as in Example 1, except that the thicknesses of the heat-sealing layer (X), the adhesive layer (Y) and the base layer (Z) were changed as shown in Table 1. The results are shown in Table 1.
[0072] Example 21 10 parts by mass of the PVA resin composition used in Example 1 was dissolved in 90 parts by mass of pure water to prepare a PVA resin composition solution. The PVA resin composition solution was applied to a polyethylene terephthalate film (substrate layer (Z)) having a thickness of 100 μm using a bar coater so that the thickness after drying would be 10 μm, and the film was dried at 100° C. for 5 minutes to obtain a heat sealable film ((X) / (Z)=PVA resin composition layer / PET=10 μm / 100 μm). The obtained heat sealable film was used to perform evaluation in the same manner as in Example 1. The results are shown in Table 1.
[0073] Example 22 A two-liquid reactive polyurethane adhesive (Mitsui Chemicals, Inc.: 24 parts by mass of "Takelac A-520" and 4 parts by mass of "Takenate A-50") was mixed with 37 parts by mass of ethyl acetate to prepare an adhesive solution (solution for adhesive layer (Y2)). The adhesive solution was applied to a 100 μm thick polyethylene terephthalate film (base layer (Z)) with a bar coater so that the thickness after drying was 2 μm, and dried at 100 ° C. for 5 minutes. Next, the PVA resin composition solution prepared in Example 21 was applied to a 10 μm thick film after drying with a bar coater, and dried at 100 ° C. for 5 minutes to obtain a heat seal film ((X) / (Y) / (Z) = PVA resin composition layer / adhesive layer / PET = 10 μm / 2 μm / 100 μm). The obtained heat seal film was used and evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0074] Example 23 A heat-sealable film was prepared and evaluated in the same manner as in Example 22, except that a VM-PET film having a 50 nm-thick aluminum metal deposition layer formed on a polyethylene terephthalate film by a known vacuum deposition method was used as a substrate layer, and the adhesive solution was applied onto the metal deposition layer. The results are shown in Table 1.
[0075] Example 24 A heat-sealable film was prepared and evaluated in the same manner as in Example 23, except that a 50 μm-thick ethylene-vinyl alcohol copolymer film (ethylene modification degree 32 mol%, saponification degree 99.9 mol%) was used as the base layer instead of the polyethylene terephthalate film. The results are shown in Table 1.
[0076] Example 25 A heat-sealable film was prepared and evaluated in the same manner as in Example 22, except that an aluminum foil having a thickness of 15 μm was used instead of the polyethylene terephthalate film. The results are shown in Table 1.
[0077] Example 26 A heat-sealable film was prepared and evaluated in the same manner as in Example 22, except that unbleached kraft paper having a thickness of 50 μm was used instead of the polyethylene terephthalate film. The results are shown in Table 1.
[0078] Comparative Example 4 A PVA resin composition and a heat-sealable film were prepared and evaluated in the same manner as in Example 1, except that PVA6 having a viscosity average polymerization degree of 1700 and a saponification degree of 98 mol% was used instead of PVA1 and no plasticizer was added. The results are shown in Table 1.
[0079] Comparative Example 5 A PVA resin composition and a heat-sealable film were prepared and evaluated in the same manner as in Example 1, except that EVOH with an ethylene modification degree of 44 mol%, a viscosity average polymerization degree of 930, and a saponification degree of 99.9 mol% was used instead of PVA1, and no plasticizer was added. The results are shown in Table 1.
[0080] [Table 1] [Industrial Applicability]
[0081] The heat-sealable film of the present invention exhibits sufficient heat-sealing properties under normal conditions of use as a packaging material, and after use as a packaging material, the heat-sealable layer can be easily dissolved and removed, and layers other than the heat-sealable layer can be separated and recovered with high purity. In addition, by selecting the base layer, it is possible to impart various functions such as required heat resistance, mechanical properties, and gas barrier properties. This makes it possible to improve the recyclability without deteriorating the performance and quality of the packaging material, and contribute to the realization of a recycling-oriented society.
Claims
1. A heat-sealable film comprising, as one outermost layer, a heat-sealable layer (X) made of a water-soluble resin composition (S), and, as the other outermost layer, a water-insoluble base material layer (Z) containing at least one selected from the group consisting of a thermoplastic resin, paper, and a metal foil, wherein the water-soluble resin composition (S) has an equilibrium moisture content of 3% by mass or more and 10% by mass or less at a temperature of 23°C and a relative humidity of 50%, the water-soluble resin composition (S) contains, as a main component, a hydroxyl group-containing resin (A) having a melting point of 220°C or less, and the water-soluble resin composition (S) contains alkali metal ions (B) in an amount of 100 ppm or more and 2000 ppm or less.
2. 2. The heat-sealable film according to claim 1, wherein the heat-sealable layer (X) is directly laminated on the base layer (Z).
3. 2. The heat-sealable film according to claim 1, further comprising an adhesive layer (Y), wherein the heat-sealable layer (X) is laminated on the base layer (Z) via the adhesive layer (Y).
4. 4. The heat-sealable film according to claim 3, wherein the heat-sealable layer (X), the adhesive layer (Y) and the base layer (Z) are a coextruded film or a part thereof.
5. The heat-sealable film according to any one of claims 1 to 4, wherein the base layer (Z) consists of a plurality of layers.
6. The heat-sealable film according to any one of claims 1 to 5, wherein the hydroxyl-containing resin (A) is a vinyl alcohol-based polymer (A1).
7. The heat-sealable film according to claim 6, wherein the vinyl alcohol polymer (A1) has a viscosity average degree of polymerization of 400 or more and 2,000 or less.
8. 8. The heat-sealable film according to claim 6, wherein the vinyl alcohol polymer (A1) has a degree of saponification of 70 mol % or more and 95 mol % or less.
9. The heat-sealable film according to any one of claims 1 to 8, wherein the water-soluble resin composition (S) contains 5% by mass or more and 40% by mass or less of a plasticizer (C), and the plasticizer (C) is at least one selected from the group consisting of glycerin, polyethylene glycol, polypropylene glycol, polyglycerin, mannitol, sorbitol, and pentaerythritol.
10. The heat-sealable film according to any one of claims 1 to 9, having a total thickness of 20 µm or more and 350 µm or less, and a thickness ratio of the heat-sealable layer (X) to the total thickness of 1% or more and 20% or less.
11. The oxygen permeability measured according to JIS K 7126-2 (isobaric method; 2006) at a temperature of 20°C and a relative humidity of 65% is 10cc / (m 2 The heat-sealable film according to any one of claims 1 to 10, wherein the heat-sealing film has a viscosity of 1000 sq. m / day atm or less.
12. The moisture permeability measured according to JIS Z 0208 (1976) at a temperature of 40°C and a relative humidity of 90% is 50 g / (m 2 The heat-sealable film according to any one of claims 1 to 11, wherein the heat-sealing time is 100 minutes or less.
13. The heat-sealable film according to any one of claims 1 to 12, wherein the heat-sealable layers (X) are placed face to face and pressed together using a hot plate heat sealer at a temperature of 185°C and a pressure of 0.1 MPa for 1 second to produce a heat seal strength of 1 N / 15 mm or more.
14. The heat-sealable film according to any one of claims 1 to 13, wherein when cut into a 2 cm square and stirred in an aqueous solution (W) at 50°C, the heat-sealable layer (X) is dissolved and removed within 5 minutes.
15. A packaging material comprising the heat-sealable film according to any one of claims 1 to 14.
16. A method for separating and recovering the heat-sealable film according to any one of claims 1 to 14, comprising contacting the film with an aqueous solution (W) at 20°C or higher and 98°C or lower to dissolve the heat-sealable layer (X), and recovering the film from which the heat-sealable layer (X) has been removed.
Citation Information
Patent Citations
Preparation of simultaneously biaxially oriented polyvinyl alcohol film
JP1979111580A
Polyvinyl alcohol laminate and manufacture thereof
JP1996112884A
Multilayered structure
JP2005081658A
Resin composition, sealant film, laminated film, packaging bag and tube container
JP2011080039A
Heat seal film and wrapper bag
JP2012041076A